A strategy for high‐dimensional multivariable analysis classifies childhood asthma phenotypes from genetic, immunological, and environmental factors. Issue 7 (31st March 2019) - Krautenbacher, Norbert; Flach, Nicolai; Böck, Andreas; Laubhahn, Kristina; Laimighofer, Michael; Theis, Fabian J.; Ankerst, Donna P.; Fuchs, Christiane; Schaub, Bianca
Abstract: Background: Associations between childhood asthma phenotypes and genetic, immunological, and environmental factors have been previously established. Yet, strategies to integrate high‐dimensional risk factors from multiple distinct data sets, and thereby increase the statistical power of analyses, have been hampered by a preponderance of missing data and lack of methods to accommodate them. Methods: We assembled questionnaire, diagnostic, genotype, microarray, RT‐qPCR, flow cytometry, and cytokine data (referred to as data modalities) to use as input factors for a classifier that could distinguish healthy children, mild‐to‐moderate allergic asthmatics, and nonallergic asthmatics. Based on data from 260 German children aged 4‐14 from our university outpatient clinic, we built a novel multilevel prediction approach for asthma outcome which could deal with a present complex missing data structure. Results: The optimal learning method was boosting based on all data sets, achieving an area underneath the receiver operating characteristic curve (AUC) for three classes of phenotypes of 0.81 (95%‐confidence interval (CI): 0.65‐0.94) using leave‐one‐out cross‐validation. Besides improving the AUC, our integrative multilevel learning approach led to tighter CIs than using smaller complete predictor data sets (AUC = 0.82 [0.66‐0.94] for boosting). The most important variables for classifying childhood asthma phenotypes comprised novel identified genes, namely PKN2 (protein kinase N2), PTK2 (protein tyrosine kinase 2), and ALPP (alkaline phosphatase, placental). Conclusion: Our combination of several data modalities using a novel strategy improved classification of childhood asthma phenotypes but requires validation in external populations. The generic approach is applicable to other multilevel data‐based risk prediction settings, which typically suffer from incomplete data. Abstract : Statistical learning on immunological, genetic, and environmental data classifies asthma well. Risk estimation is most precise when incorporating all given data with the novel multi‐modality strategy (area under the receiver operating characteristics curve = 0.81). Best predictors are three target genes of microarray data, comprising novel identified genes protein kinase N2, protein tyrosine kinase 2, and alkaline phosphatase, placental. These show the highest importance for childhood asthma classification. ALPP‐alkaline phosphatase, placental; AUC‐area under the receiver‐operator‐characteristics curve; CLARA‐clinical asthma research association; PKN2‐protein kinase N2; PTK2‐protein tyrosine kinase 2; SNP‐single nucleotide polymorphism.